Video Killed the Radio Star? Online Music Videos and Digital Music Sales - Christian Peukert; Tobias Kretschmer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Sampling poses an interesting problem in markets with experience goods. On the one hand, free samples reveal product quality and help consumers to make informed purchase decisions (promotional eff ect). On the other hand, sampling may induce consumers to substitute purchases with free consumption (displacement eff ect). We look at this trade-off in the market for digital music where consumers can sample the horizontal quality of songs by watching free music videos online. Identifi cation comes from a natural experiment in Germany, where virtually all videos that contain music are blocked on a popular video platform due to a legal dispute with representatives of the rights-holders. We show that promotional and displacement eff ects cancel out in the sales performance of songs, whereas online music videos trigger sales of albums.
Keywords: L82; M37; D83; 330